2018
DOI: 10.1175/jamc-d-17-0354.1
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of MÉRA, a High-Resolution Mesoscale Regional Reanalysis

Abstract: Met Éireann, the Irish Meteorological Service, has generated a very high resolution (2.5-km horizontal grid) regional climate reanalysis for Ireland called the Met Éireann Reanalysis (MÉRA). MÉRA spans the period from 1981 to 2015 and was produced using the shared ALADIN–HIRLAM numerical weather prediction system. This article includes comparisons with the ERA-Interim and Uncertainties in Ensembles of Regional Reanalyses (UERRA) datasets, analysis of data assimilation outputs, precipitation comparisons, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 54 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…This Met Éireann reanalysis, abbreviated MÉRA, spans the years 1981 to 2015. An analysis of surface parameters including screen-level and soil temperatures, 10-m wind speeds, mean sea-level pressure and precipitation is presented in [11,12]. This paper extends the analysis of MÉRA to include an evaluation of GHI with particular emphasis on its use in the validation of clouds.…”
Section: The Danish Networkmentioning
confidence: 99%
“…This Met Éireann reanalysis, abbreviated MÉRA, spans the years 1981 to 2015. An analysis of surface parameters including screen-level and soil temperatures, 10-m wind speeds, mean sea-level pressure and precipitation is presented in [11,12]. This paper extends the analysis of MÉRA to include an evaluation of GHI with particular emphasis on its use in the validation of clouds.…”
Section: The Danish Networkmentioning
confidence: 99%
“…ERA5 also has a greater number of vertical levels, with the first vertical level closest to the observations at 10 m. MÉRA does not assimilate satellite data, which could be important for SW or cloud properties. The skill of regional reanalyses depends on the quality of the driving reanalysis; previous studies found that MÉRA performs better than its driving reanalysis ERA-interim [19], and studies have also found that ERA5 performs better than ERA-interim [5,12,27]. Therefore, the proposed development of a new MÉRA model with ERA5 as the driving global reanalysis should lead to an improved regional scale reanalysis for Ireland.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that all three reanalyses use conventional observations in the form of surface land observations (including the temperature and wind variables) from synoptic weather stations as a source of input to the model's data assimilation process [3,19,21,22]. Therefore, the validations performed on these datasets are not truly an independent comparison.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations